Penerapan Prinsip Kehati-hatian dalam Pinjaman Online (Peer to Peer Lending) terhadap Mahasiswa di Indonesia - Edo Romario Pratama; Irma Suriyani; Kalen Sanata (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The development of financial technology has led to the emergence of online lending services based on Peer-to-Peer Lending (P2P Lending), which offer easy access to unsecured financing. However, this convenience poses significant risks when targeted at university students, who generally lack stable income and have weak financial literacy. The absence of manual verification and the suboptimal application of the prudential principle may result in a disproportionate debt burden for students. This study aims to analyze the extent to which the prudential principle is implemented by P2P Lending providers in granting loans to students, as well as to examine the legal construction of online lending agreements from a consumer protection perspective. This research employs a normative juridical method using statutory, doctrinal, and conceptual approaches. Data were obtained through literature review of relevant laws and regulations, legal literature, and supporting documents. The application of the prudential principle by P2P Lending providers remains limited and tends to focus more on user expansion than on debtor risk analysis. Online loan agreements are unilaterally drafted through standard contracts that place students in a weak legal position, without adequate protective mechanisms. Students, as vulnerable debtors, have not yet received optimal legal protection due to weak implementation of the prudential principle and exploitative contractual arrangements. Regulatory reform and strengthened oversight are necessary to ensure contractual fairness.